The Role of Neuroimaging in Our Understanding of the Suicidal Brain - Desmyter, Stefanie; Bijttebier, Stijn; Heeringen, Kees v. (CNS & Neurological Disorders - Drug Targets, 2013)
This paper provides a review of the literature on neuroimaging studies of suicidal behaviour, and discusses the relevance of these studies for our understanding of suicidal behaviour. Main findings from molecular imaging studies include a reduced prefrontal perfusion or metabolism and a blunted increase in activation when challenged in association with a history of suicide attempts. Moreover, impairment of the prefrontal serotonergic system in association with suicidal behaviour is demonstrated in a number of studies. Recent structural and functional imaging studies show changes in cortical and subcortical areas and their connections. A number of methodological issues hamper the interpretation of findings. Nevertheless, when findings from studies using divergent techniques are taken together there is increasing evidence of the involvement of a fronto-cingulo-striatal network in suicidal behaviour. This involvement is supported additionally by findings from neuropsychological studies, which demonstrate changes in decision-making processes in association with suicidal behaviour that rely on the same network. Further study is needed to translate the increasing knowledge from neuroimaging studies in clinical tools for the prediction and prevention of suicidal behaviour.
Keywords: neuroimaging